Abdullah Munsyi - a modern Malay intellectual of new century - Abdul Mutalib Embong; Ahmad Murad Merican (Proceedings of AICS - Social Sciences, 2013)
Munshi Abdullah, or  Abdullah Bin Abdul Kadir, is considered by many scholars as an early figure of modern Malay laureate  because of his against the  traditional norms writings. His two works; Kisah Pelayaran Abdullah ( The Voyage of Abdullah) ,1838 and Hikayat Abdullah ( Abdullah’s life story) , 1849,  are among his  important and meaningful chronicle memoirs in Malay literature. This paper laments Abdullah’s  true, new and different ideas which serve as a dividing line  between him and the writers before and during his time. Abdullah’s writings contain sharp criticism which addressed to the feudal and Malay community involving leadership, language and cultural practices. Such critics  arose from his education background and his social interaction with the British. It gave him new thoughts and perspectives in his writings, based on his observations and experiences which  were not rigid, comparing to  most of the conventional writings at that time, that incorporated elements of myth, fairy tales and legends. Besides, Abdullah  is also well-known for translating works into Malay, including Christian epistles for missionaries.  Some condemn Abdullah’s work  as a sign of his Anglophile persuasions, but at one level Abdullah’s criticism is inextricably related to his understanding of the weaknesses of his people. Besides his remarkable ideas, the most undeniable contribution of Abdullah is the printing work. His writings paved the way for a significant phase in the development of both Malay language and printing. He boosted the production of Malay works through his writings which previously were handwritten in manuscript forms. It was he who introduced the printing and publication of Malay books in the early  19th century and  brought great changes in the world of Malay literature. His writings brought the  analysis of Malay world which is very comprehensive and encompassing and finally become a great subject in these modern days.Keywords:Abdullah, Malay, critic, modern.